La contratación por medios electrónicos en el marco de la Comunidad Andina. Estado del arte. (2009)
The article is structured as a brief survey of the academic and policy approach on the unification or harmonization of regulations about electronic commerce, specifically relating the electronic contracts, in Latin America, with special emphasis on the Andean Community of Nations as a proposed work on the development of modern trends of international trade law.